Concentric needle jitter: Reference values in stimulated Tibialis Anterior muscle - Kouyoumdjian, João Aris; Graca, Carla Renata (Frontiers in Neurology, 2022)
Calculating the reference values for jitter parameters utilizing a disposable concentric needle have been already done for the most often tested muscles. Jitter, expressed as the mean consecutive difference (MCD), was measured in the Tibialis Anterior (TA), not routinely tested muscle. Jitter measurement was taken using the intramuscular microaxonal stimulation technique in 32 healthy subjects. The mean MCD and the mean MCD of the 27th value from the 32 subjects had a normal distribution and were 19.79 ± 2.72 μs and 26.88 ± 3.56 μs, respectively. The suggested limit for the mean MCD is ≥ 26 μs and for the individual values is > 34 μs.